Perancangan Komik Wawasan Literasi Digital untuk Anak SD - Putra Winarno, Athallah Ramadhan; Masnuna, Masnuna; Sutejo, Aris (JOEAI (Journal of Education and Instruction), 2025)
This study aims to design a digital literacy learning medium for children by using comics as an educational tool. Comics were chosen due to their visual and narrative appeal, which aligns with children's characteristics and are considered effective in delivering educational messages. The research employed a mixed-methods approach, combining quantitative methods through questionnaires and qualitative methods through interviews. The results show that comics as a learning medium can enhance children's understanding of digital literacy and help them recognize and respond to negative content on social media. In conclusion, printed comic books can serve as an engaging and educational alternative to foster digital literacy from an early age.   Keywords: comic, digital literacy, elementary school, social media